Evaluating the effects of a resistance exercise intervention for sarcopenia in patients receiving neoadjuvant chemotherapy for breast cancer: study protocol for a randomized controlled trial - Min Kyeong Jang; Seho Park; Justine Y. Jeon; Min Jae Kang; Chang Park; Ardith Z. Doorenbos; Sue Kim (BMC Cancer)
Abstract Background Sarcopenia is highly prevalent among people being treated for various types of cancers and is associated with adverse clinical impacts including postoperative complications, chemotherapy-related toxicities, and poor survival. These impacts highlight the need for early intervention to mitigate the progression of sarcopenia during treatment. To date, substantial evidence from clinical trials supports the effectiveness of resistance exercise for reducing sarcopenia, yet the specific effects of prehabilitation exercise during neoadjuvant chemotherapy among patients with breast cancer remain underexplored. Methods This two-arm randomized controlled trial (RCT) aims to evaluate the effects of a supervised resistance exercise program in addressing sarcopenia, reducing treatment-related adverse effects, alleviating cancer-related symptoms, and improving quality of life (QOL) in patients with breast cancer undergoing neoadjuvant chemotherapy. Forty-six women (aged 20 years or older, diagnosed with breast cancer, and scheduled to start neoadjuvant chemotherapy) will be randomly assigned to either a resistance exercise group or a usual care control group. To overcome potential challenges related to geographic accessibility and treatment side effects, and to improve program completion, the exercise program offers a hybrid model with three expert-supervised exercise sessions per week available both on-site and online. Each supervised session lasts 60 min. Primary and secondary outcome measures include body composition (i.e., muscle mass), muscle strength, physical performance, treatment-related adverse effects, and self-reported cancer-related symptoms and QOL. Assessments will be conducted at baseline (pre-intervention), at 6 and 12 weeks during the intervention, and at completion of the intervention (18 weeks), using validated measures. The study was approved by the institutional review board of Yonsei University Health System’s Severance Hospital. Discussion This proposed pragmatic RCT will provide meaningful insights into the role of resistance exercise in mitigating sarcopenia and its impact on the clinical outcomes of neoadjuvant chemotherapy for breast cancer. The trial is also expected to contribute to the development of evidence-based sarcopenia interventions tailored to patients with breast cancer and to help guide future directions for clinical practice and research. Trial registration This trial was prospectively registered in the Clinical Research Information Service (reference number KCT0008961) in the Republic of Korea on November 16, 2023.